Neuroprotective effects of agmatine in antineoplastic drugs induced neurotoxicity: In vitro study - ARICIOĞLU, FEYZA (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Aims: The effects of agmatine, an endogenous substance known to have a neuroprotective effect against neurotoxicity has been investigated. Material and methods: The primary neuron culture obtained from neonatal rats was exposed to toxicity with paclitaxel and cisplatin and the effect of agmatine on both acute (1 h) and chronic (24 h) exposure was demonstrated by biochemical and molecular analyses. It was demonstrated that the effect of agmatine before and after agmatine was induced by neurotoxicity before agmatine and the effect of agmatine on the formed and occuring toxicities. In addition to the results of cell viability assay, total oxidant capacity and total antioxidant capacity, we have found the opportunity to elaborate on our molecular mechanisms by elaborating our findings with apoptotic and inflammation markers such as caspase 3, kaspase 9 and TNF alpha. Key findings: The results of our study revealed the effect profile of a protective molecule against pathological neural deaths due to neurodegeneration not only in neurotoxicity due to anticancer drugs. Significance: In this context, we tried to reverse neurotoxicity due to anticancer drugs by using agmatine the duration (1 and 24 h) and dosage (10-5M and 10-6 M) determined.
Keywords: Cell culture; Cisplatin; Paclitaxel; Agmatine; TUMOR-NECROSIS-FACTOR; CISPLATIN; PACLITAXEL; BRAIN